Effect of glutathione and bovine seminal plasma in lactose extender on viability of swamp buffalo frozen semen - Sianturi, Riasari Gail; Purwantara, B; Supriatna, I; ., Amrozi; Situmorang, P (Indonesian Journal of Animal and Veterinary Sciences, 2012)
The aim of the study was to investigate the effect on viability of frozen swamp buffalo semen of glutathione and bovine seminal plasma in lactose extender. Semen from two swamp buffalo bulls was collected twice weekly using an artificial vagina. Pooled, good-quality fresh semen was divided into three parts and centrifuged at 3,000 rpm for 15 minutes in preparation for three treatments-substitution of buffalo seminal plasma with zero, 50 or 100% bovine seminal plasma (BS0, BS50 and BS100, respectively). Each semen aliquot was then divided in two parts, on which was diluted with lactose extender containing 1 mM glutathione (GSH) and the other diluted with lactose extender without GSH (0 mM GSH). Extended semen from all six treatments was cooled to 5oC and then frozen in 0.25 ml straws.Â  Mean motility percentages 0 and 30 minutes post thaw (PTM 0â² and 30â²) with GSH were 38.33 and 34.29%, significantly higher (P < 0.05) than treatments without GSH (31.67 and 25.95%). PTM 0â² and 30â² were also higher (P < 0.05) with no substitution of bovine seminal plasma (BS0) than when buffalo seminal plasma was replaced with bovine seminal plasma at either 50 or 100%. Averages were 40.00 vs 34.46 and 30.54% (BS0 vs BS50 and BS100) at thawing and 36.96 vs 28.36 and 25.36% 30 minutes post-thaw. Mean percentages of live sperm (LD), intact plasma membrane (MPU) and intact acrosomal membrane (TAU) at thawing were not significantly different with or without addition of GSH. However,at 30â² post thawing, TAU and MPU were significantly higher in GSH treatments than inthose without GSH:Â  61.50 vs. 58.19% (MPU) and 59.81 vs. 57.38% (TAU). Mean percentages of LD, TAU and MPU 30â²post thawing were higher with no substitution ofbuffalo seminal plasma (BS0) (P < 0.05) than to BS50 and BS100 treatments. In conclusion, the addition of glutathione (GSH) improved the quality of frozen swamp buffalo semen, but the partial substitution of buffalo seminal plasma with bovine seminal plasmaprovided no beneficial effects. Key Words: Swamp buffalo, Semen, Antioxidant, Glutathione, Seminal plasma